Recalled Experience of Death: transcending the cerebrocentric model of consciousness - Armando Henrique Norman; Gabriela Bley Jacob (Interface: Comunicação, Saúde, Educação)
To explore the scientific approach to Recalled Experience of Death (RED) and correlate it with the philosophical foundations of Family and Community Medicine to expand the understanding of the human consciousness. Non-systematic review on PubMed database for relevant “prospective studies” on “near-death experience”. Five prospective studies documented RED phenomenon occurrences during clinical death. RED-studies strengthen an organismic model of existence and challenge consciousness concept as epiphenomenon of brain activities. This prompts a new understanding of mind-brain relationship inspired by quantum mechanics unified informational field, i.e., consciousness as non-local. This knowledge can help healthcare professionals in dealing with patients with existential problems as in mental health, palliative care, and spiritual issues. RED-studies epitomise a pre-paradigmatic stage in the construction of a new concept of human consciousness in relation to the brain.